Influence of energy loss of implant with wireless power supply on the thermal state of the body - Володимир Петрович Олійник; Дар’я Вікторівна Теличко; В’ячеслав Миколайович Олійник (Radìoelektronnì ì komp'ûternì sistemi (Online), 2021)
Technical means that create for regenerating lost functions of the human body primarily focused on the target function. However, even when implants achieve performance that corresponds to natural organs and systems, in many cases the developers do not pay enough attention to the energy supply of implants and additional heat load due to energy losses in mechanical, electrical, and electronic units. If you do not consider these factors, it limits the duration and medical safety of the devices. It is especially true for implants with significant power consumption and wireless power supply. Therefore, this work determines the allowable additional heat load of the human body to justify the choice of further circuit solutions for wireless powering of implants with significant energy consumption and long-term operation. The subject of research is the processes of heat exchange between the implant and body structures and their energy and temperature indicators. The research object was chosen as an implant of the type "Artificial Heart" device (AHD) with a maximum power of 20… 25 W and the magnetic induction principle of energy transfer. The research tasks are to analyze the processes of heat exchange between the implant and the biostructures of the body; to calculate quantitative indicators of energy exchange in the location of the main components of the implant; to determine the temperature of biotissues in the area of the receiving inductor. The subject of research is the processes of heat exchange between the implant and body structures and their energy and temperature indicators. The research object was chosen as the implant of the type "Artificial Heart" device (AHD) with a maximum power of 20… 25 W and the magnetic induction principle of energy transfer. The research tasks are to analyze the processes of heat exchange between the implant and the biostructures of the body; to calculate quantitative indicators of energy exchange in the location of the main components of the implant; to determine the temperature of biotissues in the area of the receiving inductor. Research results. The processes of heat exchange between the structural elements of the implant and the biostructures of the body have a complex combination of physiological and physical mechanisms. Estimates are made based on the thermal conductivity process, as the most objective in terms of known quantitative indicators. With an average efficiency of ~ 0.8 for mechanical, electrical, and electronic components of the implant "Artificial Heart," the human body can maintain a stable temperature of internal organs in the presence of an implant with a maximum power consumption of 20 watts. The calculation conducted using the method of electrothermal analogy showed a possible increase in the temperature of biotissues in contact with the surface of the receiving implanted inductor, by 1.32 ° C. This value refers to the critical levels of internal tissue temperature rise. Summary. For practical implementation of the autonomous device the Artificial Heart Device, it is necessary to combine known or to find the original circuit-technical and design decisions of construction of components of wireless power supply with the magnetic induction principle and efficiency of not less than 0,8. To prevent thermal overload of biotissues, it is advisable to introduce a temperature control channel at potentially critical locations of the implanted elements. It is possible to predict the finding of these critical points by calculations by the method of electrothermal analogy.